Sensing period considerations in fading environment for multimedia delivery in cognitive Ultra Wideband system - Rashid R.A.; Aripin N.M.; Fisal N.; Yusof S.K.S. (2023)
Spectrum scarcity and the inefficiency in its usage have necessitates the use of Cognitive Radio (CR) technology to exploit the existing wireless spectrum opportunistically. Spectrum sensing is a critical component of CR as it is a fundamental requirement that a cognitive user (CU) continuously senses the channel before accessing it to avoid causing interference to the primary user (PU) and other radio systems. Due to its low transmit power, detection of PU in a fading environment for an Ultra Wideband (UWB) system is a key problem. This paper presents preliminary works in determining the appropriate sensing period for the cognitive UWB that support multimedia delivery. Firstly, the proposed cross-layer design for multimedia transmission is presented. Next, simulations of bit-error-rate (BER), packet-error-rate (PER) and job-failure-rate (JFR) were carried out to determine the optimal signal-to-ratio (SNR) range to meet the Quality-of-Service (QoS) requirement set for video application. Lastly, the performance of probability of detection against SNR is studied to estimate the appropriate time slot allocation for sensing scheduling.